KEMAMPUAN SISWA MENARI BEDANA MELALUI METODE LATIHAN DI SMP NEGERI 2 SEPUTIH MATARAM - Dian Yulianawati; Susi Wendhaningsih; Ni Nyoman Wetty (Jurnal Seni dan Pembelajaran, 2013)
The problem of this research was how is the students’ ability in dancing Bedanathrough classroom exercise at the grade of VIII A of SMP Negeri 2 SeputihMataram. Related to that problem, this research was aimed to describe thestudents’ ability in dancing Bedana through exercise method.The method of he research was field study and book. The approach of the researchwas descriptive qualitative. The sources of the data were the 36 students of gradeVIII A. the technique of the research was observation, interview, and test ofstudents’ ability. The observation that was done by the researcher was theobservation of students’ activity and students’ learning achievement. The researchinstrument that was used in scoring the students’ Bedana dance were wiragaindicator (technique and memorizing sub indicator), wirama indictor (tempoaccuracy and movement sequence sub indicator) and wirasa (face expression).The result of this research shows that the students’ ability in dancing Bedanathrough exercise method categorized as sufficient. It was concluded as sufficientsince there were 3-4 faults of wiraga, wirama, and wirasa aspects. The students’average score was 69. The average score of wiraga indicator was 72, while theaverage score of wirama indicator was 69 and the wirasa indicator average scorewas 63.Keywords: ability, education, exercise method, Bedana dance.